2021
DOI: 10.3390/jcm10214892
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality and Stomatognathic System Disorders in Physiotherapy Students during the COVID-19 Pandemic

Abstract: Background: A person’s response to stressors is largely dependent on their personality traits that affect the way stress is controlled and relieved. This article is a quantitative analysis assessing the importance of the distressed personality in the development of stomatognathic system disorders (SSDs) in physiotherapy students during the COVID-19 pandemic. Objective: The goal of the research was to assess the presence of type D personality in students with symptoms of stomatognathic system disorders. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Personality is one of the most important determinants influencing the behavior and functioning of an individual. Earlier research results confirm the influence of a type D personality on the occurrence of TMD symptoms of TMD during the COVID-19 pandemic [ 46 , 47 ]. According to the present study, people diagnosed with stress personality types reported a greater number of TMD symptoms compared to people without this personality trait ( p = 0.00).…”
Section: Discussionsupporting
confidence: 57%
“…Personality is one of the most important determinants influencing the behavior and functioning of an individual. Earlier research results confirm the influence of a type D personality on the occurrence of TMD symptoms of TMD during the COVID-19 pandemic [ 46 , 47 ]. According to the present study, people diagnosed with stress personality types reported a greater number of TMD symptoms compared to people without this personality trait ( p = 0.00).…”
Section: Discussionsupporting
confidence: 57%
“…According to Gębska et al, people with stressed personality (type D) had symptoms of SSD disorders significantly more often than in the group without stress personality traits. In the group of people with personality D, the most frequently reported symptoms of SS disorders were headache (51.3%), pain in the neck and shoulder girdle (43.1%), and tooth clenching (35.6%) [41]. In our study, a higher level of conscientiousness was statistically significantly associated with the occurrence of teeth clenching and a high level of neuroticism.…”
Section: Discussionsupporting
confidence: 48%
“…Teachers faced the challenge trying to teach the core competencies of their subjects through online teaching ( 7 , 8 ). In addition, the physiotherapy students had to cope with the psychosocial issues arising from the pandemic ( 9 , 10 ) while getting used to the new teaching modalities ( 6 ).…”
Section: Introductionmentioning
confidence: 99%